Coffee Bench - Shahril Azlan, Alyaa Farzana; Mohd Arrif, Hamim; Alias, Najeeha Nasya; Mohd Nor, Nur Nazeiha; Noor Azman, Puteri Nur Balqis; Mohamed Shahrum, Nurul Syafarahin (2015)
Coffee Bench is located at No 89, Jalan S2, E4 Garden Homes, 70300, Seremban, Negeri Sembilan, and specializes in producing and selling multifunctional coffee benches. These benches are manufactured using our own unique designs to provide comfort to users. The company was registered on 1st October 2015, and operations commenced on 10th January 2016. Seremban was selected as the location because it is a strategic commercial hub situated close to economic centers, transport facilities, schools, and hospitals. Consequently, this location was chosen to introduce our product as a distinctive offering in the furniture industry. Our motto, "Creating comfort and style for you," aligns with our aim to ensure the product is comfortable and user-friendly. Additionally, we provide a unique product that combines the features of a chair and a bench, designed to help customers save time and space. We manufacture based on customer demand to ensure satisfaction, which reflects our customer-centric priority. Finally, we anticipate generating profit and building customer trust, with the capability to produce various designs and a vision to expand outlets nationwide to become a well-known entity in the furniture industry.